Changes in serum level of ghrelin, tumor necrosis factor-alpha and interleukin-6 in children with congenital heart disease - Yadav, Shiv Kumar; YI, Qi jian (Asian Journal of Medical Sciences, 2015)
Objective: To investigate the changes in serum levels of ghrelin, tumor necrosis factor-α and interleukin-6 in Children with Congenital Heart Disease (CHD) at pre and post percutaneous management of the lesions. Material & Methods: We measured the serum levels of ghrelin, tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) by enzyme linked immunosorbent assays (ELISA) in 67 patients with CHD and in 20 control subjects; and compared these markers of inflammatory reaction between groups of pre-closure (37 patients) and at the end of 5 minutes (37 patients), 1 month (22 patients) and 3 month (8 patients) post percutaneous management of the lesions. Results: Our results showed that the patients with CHD had significantly higher serum level of Ghrelin, TNF-α and IL-6 in comparison of the controls but gradually return towards the baseline levels at the end of 3 months post percutaneous management of the lesions. Conclusion: The inflammatory reaction is activated in pre-closure and self-limited post-closure in children with CHD. Percutaneous management could improve the inflammatory process, which is safe and effective in children with CHD. DOI: http://dx.doi.org/10.3126/ajms.v6i5.12129 Asian Journal of Medical Sciences Vol.6(5) 2015 12-16